PV Power Output Control Improving Transient Stability of Power System with a Large Penetration of PV. Issue 4 (March 2017) - MITSUGI, YASUAKI; YOKOYAMA, AKIHIKO; YAMADA, SEIJI; TANIKAWA, TOMOYA
SUMMARY: Because of energy and environmental policies in the last decade, a lot of photovoltaic (PV) generations have been installed into power systems in Japan in recent years. In this situation, it is of great concern that disconnection of PV due to voltage drop caused by a system fault has a critical impact on power system stability. To avoid its disconnection, Fault Ride Through (FRT) requirement is applied for PVs. In this paper, PV power output control which improves transient stability of the power system with a huge amount of PVs is proposed and its effectiveness is confirmed by the numerical simulations.